Interspecific urochloa breeding program: Technical report - A521 - Mejia, Juan Camilo (2024)
The genetic gain of yield, seed yield, and nutritional quality in the interspecific Urochloa pipeline was estimated through an ERA trial conducted at the CIAT campus in Palmira, Colombia. Each trial included 150 genotypes from seven cycles of selection at different stages, along with genebank accessions and cultivars. The assessed traits were shoot dry weight (SDW), cover (calculated from drone images), seed gross yield (SGY), crude protein content (CP), neutral detergent fiber content (NDF), and acid detergent fiber content (ADF). For the genetic gain estimation, we used a two-stage approach, considering only the hybrids in stage 4, which were selected after multi-location trials in Latin America by the Papalotla Group company (PG). Genetic gain rates were positive for SGY, SDW, and CP. Conversely, NDF and ADF showed negative genetic gain values, as the objective of these traits is to reduce them by improving the percentage of protein content and enhancing nutritional quality of the crop.